Political capitalism : how economic and political power is made and maintained - Holcombe, Randall G. (Cambridge : Cambridge University Press, 2018)
Problems associated with cronyism, corporatism, and policies that favor the elite over the masses have received increasing attention in recent years. Political Capitalism explains that what people often view as the result of corruption and unethical behavior are symptoms of a distinct system of political economy. The symptoms of political capitalism are often viewed as the result of government intervention in a market economy, or as attributes of a capitalist economy itself. Randall G. Holcombe combines well-established theories in economics and the social sciences to show that political capitalism is not a mixed economy, or government intervention in a market economy, or some intermediate step between capitalism and socialism. After developing the economic theory of political capitalism, Holcombe goes on to explain how changes in political ideology have facilitated the growth of political capitalism, and what can be done to redirect public policy back toward the public interest.
The concept of political capitalism -- Political capitalism as an economic system -- The political and economic elite -- Interest groups and political exchange -- Political creation of economic rents -- Transitional gains and rent extraction -- The regulatory state -- Capitalism versus democracy -- The institutional evolution of political capitalism -- Public policy and political capitalism -- Is political capitalism inevitable?
Title from publisher's bibliographic system (viewed on 25 Jul 2018).
Keywords: Capitalism -- Political aspects; Power (Social sciences)